Sistemi delitve dela v bolnišnični zdravstveni negi - Šmitek, Jana (Obzornik zdravstvene nege, 2000)
The formation of an adequate system or model of task delegation in hospital practice is a responsible task of nursing management. The article presents, from the point of view of strong and weak points, traditional systems of task delegation in nursing care-the system of holistic nursing care of individual patients, multiple patient assignment, functional model, team system and system of primary nursing care. Among alternative models, typical case management as a variety of better organized systems of task delegation is described. The article also presents the evaluation of existing systems in nursing care in Slovenia, together with theoretical directions that could influence the development of new approaches to hospital nursing care.
Keywords: Case management; Classification; Nursing care; Nursing process; Nursing service, hospital; Nursing, team; organizacija; organization; Task performance and analysis; teamsko delo; zdravstvena nega